Zinc based biodegradable metals for bone repair and regeneration: Bioactivity and molecular mechanisms - Ping Li; Jingtao Dai; Yageng Li; Dorothea Alexander; Jaroslav Čapek; Jürgen Geis-Gerstorfer; Guojiang Wan; Jianmin Han; Zhentao Yu; An Li (Materials Today Bio, 2024)
Bone fractures and critical-size bone defects are significant public health issues, and clinical treatment outcomes are closely related to the intrinsic properties of the utilized implant materials. Zinc (Zn)-based biodegradable metals (BMs) have emerged as promising bioactive materials because of their exceptional biocompatibility, appropriate mechanical properties, and controllable biodegradation. This review summarizes the state of the art in terms of Zn-based metals for bone repair and regeneration, focusing on bridging the gap between biological mechanism and required bioactivity. The molecular mechanism underlying the release of Zn ions from Zn-based BMs in the improvement of bone repair and regeneration is elucidated. By integrating clinical considerations and the specific bioactivity required for implant materials, this review summarizes the current research status of Zn-based internal fixation materials for promoting fracture healing, Zn-based scaffolds for regenerating critical-size bone defects, and Zn-based barrier membranes for reconstituting alveolar bone defects. Considering the significant progress made in the research on Zn-based BMs for potential clinical applications, the challenges and promising research directions are proposed and discussed.